2009
DOI: 10.1038/ni.1720
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy enhances the presentation of endogenous viral antigens on MHC class I molecules during HSV-1 infection

Abstract: Viral proteins are usually processed by the ‘classical’ major histocompatibility complex (MHC) class I presentation pathway. Here we showed that although macrophages infected with herpes simplex virus type 1 (HSV-1) initially stimulated CD8+ T cells by this pathway, a second pathway involving a vacuolar compartment was triggered later during infection. Morphological and functional analyses indicated that distinct forms of autophagy facilitated the presentation of HSV-1 antigens on MHC class I molecules. One fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
413
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(429 citation statements)
references
References 43 publications
12
413
1
2
Order By: Relevance
“…A pertinent example is the role of autophagy in facilitating MHCI presentation by herpes simplex virus 1 (HSV-1) infected macrophages, 8-12 h after infection (English et al, 2009). At these time points, treatment of HSV-1 infected macrophages with bafilomycin A (an inhibitor of lysosomal acidification), 3-MA or knockdown of Atg5, im-pairs HSV-1 glycoprotein B (gB)-specific CD8 + T cell activation, indicating that at this stage of infection both autophagosomes and lysosomal degradation are required for gB MHCI antigen presentation (English et al, 2009). Using fluorescence and electron microscopy, LC3+ autophagosomes are observed to originate from the nuclear envelope containing HSV-1 particles (English et al, 2009).…”
Section: Autophagy In Classical Mhc Class I Antigen Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…A pertinent example is the role of autophagy in facilitating MHCI presentation by herpes simplex virus 1 (HSV-1) infected macrophages, 8-12 h after infection (English et al, 2009). At these time points, treatment of HSV-1 infected macrophages with bafilomycin A (an inhibitor of lysosomal acidification), 3-MA or knockdown of Atg5, im-pairs HSV-1 glycoprotein B (gB)-specific CD8 + T cell activation, indicating that at this stage of infection both autophagosomes and lysosomal degradation are required for gB MHCI antigen presentation (English et al, 2009). Using fluorescence and electron microscopy, LC3+ autophagosomes are observed to originate from the nuclear envelope containing HSV-1 particles (English et al, 2009).…”
Section: Autophagy In Classical Mhc Class I Antigen Presentationmentioning
confidence: 99%
“…At these time points, treatment of HSV-1 infected macrophages with bafilomycin A (an inhibitor of lysosomal acidification), 3-MA or knockdown of Atg5, im-pairs HSV-1 glycoprotein B (gB)-specific CD8 + T cell activation, indicating that at this stage of infection both autophagosomes and lysosomal degradation are required for gB MHCI antigen presentation (English et al, 2009). Using fluorescence and electron microscopy, LC3+ autophagosomes are observed to originate from the nuclear envelope containing HSV-1 particles (English et al, 2009). The authors suggest that gB processing begins in the autophagosome after which gB peptides escape to the cytosol for further processing by the proteasome and entry into the MHCI antigen presentation pathway.…”
Section: Autophagy In Classical Mhc Class I Antigen Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In autophagosome viral proteins undergo further processing by the proteasome for MHC presentation [37,38]. It has been shown that altered HSV-1 gene transfer to neuronal cells leads to the induction of MHC-I and MHC-II, which drives inflammatory effects characterized by the recruitment of activated T cells and macrophages [143].…”
Section: Altered Mhc Response During Viral Infectionmentioning
confidence: 99%
“…Both rough ER and the outer nuclear leaflet have been identified as autophagosome formation sites [13][14][15] , but these vesicles might also be generated at other places. Two ubiquitin-like systems are involved in autophagosome formation at these sites with Atg8 and Atg12 as the ubiquitin-like molecules at their center 16 .…”
Section: T Cells Detect Infected or Transformed Cells Via Antigen Prementioning
confidence: 99%